2018
DOI: 10.5604/01.3001.0012.4894
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma and Associated Clinical Features in Latino and Caucasian Patients from a Single Center

Abstract: Introduction and aim. Hepatocellular carcinoma (HCC) is the most common type of liver cancer in adults and has seen a rapid increase in incidence in the United States. Racial and ethnic differences in HCC incidence have been observed, with Latinos showing the greatest increase over the past four decades, highlighting a concerning health disparity. The goal of the present study was to compare the clinical features at the time of diagnosis of HCC in Latino and Caucasian patients. Material and methods. We retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…This finding is similar to previous studies reported in different countries or continents, which indicates HCC as a global problem worldwide. 12,13 In general, the prevalence of hepatitis B in Indonesia is higher than other hepatitis infections and hepatitis B is the most common etiology of HCC, as previously reported. 9,14 Furthermore, the most common symptom in HCC patients in our study was abdominal pain, consistent with the study from Saudi Arabia.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This finding is similar to previous studies reported in different countries or continents, which indicates HCC as a global problem worldwide. 12,13 In general, the prevalence of hepatitis B in Indonesia is higher than other hepatitis infections and hepatitis B is the most common etiology of HCC, as previously reported. 9,14 Furthermore, the most common symptom in HCC patients in our study was abdominal pain, consistent with the study from Saudi Arabia.…”
Section: Discussionmentioning
confidence: 62%
“…18 Albumin levels in this study were found to be decreased in most patients, which is consistent with finding from the United States. 13 In this study, most of the patients had multinodular tumors. However, a study in Jakarta resulted that singular nodules were more common than multiple.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, the relationship between obesity and HCC risk may differ according to ancestry, with a greater association among Americans, Japanese, whites, and Latin American men but not in African-descendant men; and may be related to ancestry and gender variances in fat body distribution (35) . A previous study suggested that obesity was positively associated with HCC in whites, but not in African Americans (1,41) . Compared to whites in similar conditions, Latinos and Asians are more likely than African Americans to accumulate fatty cells in the abdominal visceral compartment and the liver (1,41) .…”
Section: Ancestry / Racementioning
confidence: 89%
“…Our study found that Hispanics were significantly less likely to receive PC than NHWs. This finding is particularly concerning given that the burden of HCC among the Hispanic population has been growing steadily, and Hispanics now have 2.5 times the incidence of HCC than NHW 20–24 . Several social determinants of health may explain this PC utilization disparity, including medical literacy/language barriers and ability to access high‐quality cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is particularly concerning given that the burden of HCC among the Hispanic population has been growing steadily, and Hispanics now have 2.5 times the incidence of HCC than NHW. [20][21][22][23][24] Several social determinants of health may explain this PC utilization disparity, including medical literacy/language barriers and ability to access high-quality cancer care. A 2019 study of the National Cancer Institute's Health Information National Trends Survey found that 85% of Hispanic patients had no knowledge about PC.…”
Section: Discussionmentioning
confidence: 99%